Synergetic effect of Panchakarma based treatment regimen for Parkinson’s disease with special reference to Kampa vata: A case report - Nilani, K.K.A.; Gunarathna, E.D.T.P. (University of Colombo, 2025)
Parkinson’s disease is a chronic, progressive neurodegenerative disorder affecting millions globally. In Ayurvedic literature, Parkinson’s disease has clinical resemblance to Kampa vata, characterized by tremors, rigidity and bradykinesia. This case study aims to evaluate the efficacy of a Panchakarma-based treatment protocol described in Cikitsa Sarasangraha, an Ayurvedic text authored by Vangasena in 1276 A.D. A 47-year-old female patient diagnosed with Kampa vata presented to the Ayurveda National Hospital, Borella, with symptoms including tremors of the upper and lower limbs (Karapadatala Kampa), rigidity (Stambha), slowness of movement (Chestasanga) and postural instability (Dehabramana) persisting for three years. With informed consent, the patient underwent a 35-day Panchakarma treatment regimen. The protocol included: Abhyanga and Swedana with Kshirabala taila and Dashamuladi nadi swda for 7 days; Yoga vasti comprising Kshirabala taila anuvasana vasti and Atmagupatadi niruha vasti for 8 days; Shirovasti with Kshirabala taila for 7 days; and Virechana karma with 30 ml Eranda taila mixed with 60 ml Triphala decoction as the concluding therapy. The patient was assessed before and after the treatment using Hoehn and Yahr Scale and Parkinson’s disease composite scale. The patient showed mild to moderate degree of improvement in the symptoms. Hoehn and Yahr Scale changed from stage 03 to stage 02 within 20 days and Parkinson’s disease composite scale also showed some changes which tremor 66%, rigidity 66%, bradykinesia 66% and postural instability 66% were reduced. Sarvanga abhyanga, Anuvasana vasti and Shirovasti with Kshirabala taila helped in reducing stiffness of muscles and joints, providing analgesic effect, nourishment of Sushka dhathu and also doing Vatahara and Vatanulomana action with neuro protective action. This case study suggests that the Panchakarma therapies outlined in Vangasena Samhita offer a promising integrative approach for managing Kampa vata and its parallels with Parkinson’s disease. Further clinical studies are needed to validate these findings and explore the broader therapeutic potential of Ayurvedic management in Kampa vata
Keywords: Panchakarma; Kampa vata; Parkinson’s disease; Vatanulomana